Mamá Antula: la beata de los ejercicios espirituales desde la mirada de los jesuitas desterrados. - FERNÁNDEZ ARRILLAGA, INMACULADA (Scripta, 2016)
When in 1767 Charles III of Spain expelled the Jesuits, a devout woman: Maria Antonia de San José, continued their work focusing on the realization of the Ignatian Spiritual Exercises along the Province of Paraguay. We analyze in this easy the inluence of these religious on her missionary activity and the comments they wrote during their exile.